The conjugate harmonic functions in problems for the Laplace equation - E. М. Kartashov (Тонкие химические технологии, 2014)
A method of conjugate harmonic functions in solving boundary value problems for Laplace’s equation in two dimensions was developed. A series of illustrative problems was considered.